Using the distributive property, we multiply each term in the first parentheses by each term in the second parentheses:
(x+8)(x-2) = x(x-2) + 8(x-2)
= x * x - x * 2 + 8 * x - 8 * 2
= x^2 - 2x + 8x - 16
= x^2 + 6x - 16
Use the Distributive Property to rewrite the polynomial (x+8)(x−2)
.(2 points)
5 answers
thats not the answer:(
Apologies for the mistake. Let's solve it correctly:
Using the distributive property, we multiply each term in the first parentheses by each term in the second parentheses:
(x+8)(x-2) = x(x) + x(-2) + 8(x) + 8(-2)
= x^2 - 2x + 8x - 16
= x^2 + 6x - 16
Using the distributive property, we multiply each term in the first parentheses by each term in the second parentheses:
(x+8)(x-2) = x(x) + x(-2) + 8(x) + 8(-2)
= x^2 - 2x + 8x - 16
= x^2 + 6x - 16
Rewrite the expression 3x(x + 3)
using the Distributive Property.(1 point)
using the Distributive Property.(1 point)
Using the distributive property, we multiply each term inside the parentheses by the term outside the parentheses:
3x(x + 3) = 3x * x + 3x * 3
= 3x^2 + 9x
3x(x + 3) = 3x * x + 3x * 3
= 3x^2 + 9x